2022
DOI: 10.1007/s10341-022-00764-w
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of a Wild-Type Population of Cornelian Cherries (Cornus mas L.) from Austria

Abstract: Cornelian cherry (Cornus mas L.) belongs to a group of fruit and nut species growing in Europe considered to be underused economically, although it has been recognized as a potential regional “superfood” and as a source of valuable bioactive compounds. Phenotyping fruits of 30 accessions of an Austrian wildtype population of C. mas allowed to evaluate their nutraceutical potential. Ten fruits per accession were characterized by morphological and morphometric approaches. Biochemical analyses were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Over 650 different anthocyanins have been isolated in plants with six possible aglycon structures (anthocyanidins) most frequently occurring in natural conditions: pelargonidin, cyanidin, peonidin, delphinidin, petunidin, and malvidin [ 26 ]. Qualitative analyses of anthocyanins in cornelian cherry most often reveal the presence of cyanidin 3- O -galactoside [ 27 , 28 , 29 , 30 ], cyanidin 3- O -robinobioside [ 25 , 31 , 32 ], pelargonidin 3- O -galactoside [ 27 , 28 ], pelargonidin 3- O -robinobioside [ 25 , 31 ] and delphinidin 3- O -galactoside [ 29 , 33 ]. In addition, there are peonidin 3- O -glucoside [ 33 , 34 ] and petunidin 3- O -glucoside [ 31 , 33 ], with no reports of anthocyanins derived from malvidin ( Figure 2 ).…”
Section: Bioavailability and Bioefficacy Of Anthocyanins Derived From...mentioning
confidence: 99%
“…Over 650 different anthocyanins have been isolated in plants with six possible aglycon structures (anthocyanidins) most frequently occurring in natural conditions: pelargonidin, cyanidin, peonidin, delphinidin, petunidin, and malvidin [ 26 ]. Qualitative analyses of anthocyanins in cornelian cherry most often reveal the presence of cyanidin 3- O -galactoside [ 27 , 28 , 29 , 30 ], cyanidin 3- O -robinobioside [ 25 , 31 , 32 ], pelargonidin 3- O -galactoside [ 27 , 28 ], pelargonidin 3- O -robinobioside [ 25 , 31 ] and delphinidin 3- O -galactoside [ 29 , 33 ]. In addition, there are peonidin 3- O -glucoside [ 33 , 34 ] and petunidin 3- O -glucoside [ 31 , 33 ], with no reports of anthocyanins derived from malvidin ( Figure 2 ).…”
Section: Bioavailability and Bioefficacy Of Anthocyanins Derived From...mentioning
confidence: 99%
“…Vitamin C helps maintain a healthy immune system, vitamin K affects bone health, and vitamin A plays an important role in vision and skin health. Also, dogwood contains antioxidants such as anthocyanins and flavonoids that help protect cells from free radical damage (11) . The various flavonoids that dogwood berries contain vary depending on the variety and maturity of the fruit (12) : 1.…”
Section: Benefits Of Using Berries In Soft Drinks (Including Energy D...mentioning
confidence: 99%
“…Thus, the ripe fruits were used to treat sore throats, gastrointestinal disorders, measles, chicken pox, anemia, rickets, fever, inflammation, skin disorders, tuberculosis, malaria, cancer, thermic fever, wounds, liver diseases such as hepatitis A and kidney diseases such as pyelonephritis and renal calculi [ 16 , 21 ]. In recent years, the effects of Cornus mas L. fruits have been the subject of numerous studies, which have revealed that they have anti-inflammatory, antibacterial, antioxidant, antidiabetic, antiatherosclerotic, antiproliferative, antiparasitic, antihyperlipidemic, nephroprotective, hepatoprotective and neuroprotective effects [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%